2013
DOI: 10.1371/journal.ppat.1003384
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Upregulates the Cellular Deubiquitinase UCHL1 to Suppress the Keratinocyte's Innate Immune Response

Abstract: Persistent infection of basal keratinocytes with high-risk human papillomavirus (hrHPV) may cause cancer. Keratinocytes are equipped with different pattern recognition receptors (PRRs) but hrHPV has developed ways to dampen their signals resulting in minimal inflammation and evasion of host immunity for sustained periods of time. To understand the mechanisms underlying hrHPV's capacity to evade immunity, we studied PRR signaling in non, newly, and persistently hrHPV-infected keratinocytes. We found that active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
159
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 50 publications
6
159
0
1
Order By: Relevance
“…Although the expression level of exogenous E1 in our experiments could be much higher than that during initial amplification, a lower level of E1 might be sufficient to induce NF-B activation. Karim et al reported that an increase in NF-B activity was detected within 24 h after infection with HPV16 virions isolated from raft cultures (50). Although their interpretation was that NF-B is activated as part of an innate immune response, their results did not exclude the possibility that E1-dependent initial amplification contributes to activation of NF-B.…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the expression level of exogenous E1 in our experiments could be much higher than that during initial amplification, a lower level of E1 might be sufficient to induce NF-B activation. Karim et al reported that an increase in NF-B activity was detected within 24 h after infection with HPV16 virions isolated from raft cultures (50). Although their interpretation was that NF-B is activated as part of an innate immune response, their results did not exclude the possibility that E1-dependent initial amplification contributes to activation of NF-B.…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 96%
“…ATM has been shown to activate the IB kinase (IKK) complex by directly phosphorylating its regulatory subunit, the NF-B essential modulator (NEMO), and this activation of IKK leads to phosphorylation-dependent degradation of IB␣ (49). Interestingly, it was recently shown that degradation of NEMO is enhanced in human keratinocytes containing episomal HPV16 genomes, compared to primary human keratinocytes (50). Therefore, activation of NF-B by the ATM-mediated pathway through NEMO could be inherently limited in HCK1T-HPV16 cells.…”
Section: Activation Of Nf-b By E1 Through Ddrmentioning
confidence: 99%
“…Moreover, many of these vaccines are directed against viral structures involved in malignant transformation (Table 2). This advantage can be exploited, because the vaccine can deliver antigen and stimulate robust effector T cell responses, whereas the natural infection is subject to the myriad intricate immune evasion and immunosuppression mechanisms these viruses have developed in the course of evolution (92)(93)(94)(95)(96)(97)(98). Nevertheless, these vaccines have to work against the same peripheral cell tolerance-, anergy-, and suppression-driving mechanisms operating in nononcogenic, persistent viral infections and nonviral cancers.…”
Section: Clinical Cancer Vaccines Against Nonviral Antigensmentioning
confidence: 99%
“…UCHL1 proved to be a potent negative regulator of PRR-induced immune responses in KC and was exploited by high-risk HPV to prevent the production of IFNs, cytokines, and chemokines and the attraction of professional immune cells. Mechanistic studies showed that UCHL1-mediated suppression of nuclear factor B (NF-B) and IFN response factor (IRF) signaling pathways by destabilizing NF-B essential modulator and preventing polyubiquitination of TNF receptor-associated factor 3, respectively (43). HPV-transformed KC tend to lose expression of UCHL1, suggesting that different mechanisms of immune escape operate in these cells.…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 99%
“…KC constitutively secrete low levels of soluble immune mediators, including cytokines, chemokines, and growth factors (46)(47)(48), the production of which can be elevated in response to proinflammatory stimuli, including PRR activation and autocrine or paracrine stimulation with inflammatory cytokines (31,43,46,47,49). Several cytokines, including type I IFNs, TNF-␣, IL-1␣, IL-4, IL-13, and transforming growth factor ␤ (TGF-␤), share the ability to inhibit HPV early gene expression (50)(51)(52)(53)(54).…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 99%